Gonad Transcriptome Analysis of the Razor Clam (Sinonovacula constricta) Revealed Potential Sex-Related Genes - Yao, Hanhan; Lin, Zhihua; Dong, Yinghui; Kong, Xianghui; He, Lin; Xue, Liangyi (Frontiers in Marine Science, 2021)
The razor clam, Sinonovacula constricta is a commercially important bivalve in the western Pacific Ocean, yet little is known about the mechanisms of sex determination/differentiation and gametogenesis. In the present study, the comparative transcriptome analysis of adult gonads (female gonads and male gonads) was conducted to identify potential sex-related genes in S. constricta. The number of reads generated for each target library (three females and three males) ranged from 31,853,422 to 37,750,848, and 20,489,472 to 26,152,448 of could be mapped to the reference genome of S. constricta (the map percentage ranging from 63.71% to 71.48%). A total of 8497 genes were identified to be differentially expressed between the female and male gonads, of which 4253 were female-biased (upregulated in females), and 4244 were male-biased. Forty-five genes were identified as potential sex-related genes, including DmrtA2, Sox9, Fem-1b and Fem-1c involved in sex determination/differentiation and Vg, CYP17A1, SOHLH2, and TSSK involved in gametogenesis. The expression profiles of twelve genes were validated by qRT-PCR, which further confirmed the reliability and accuracy of the RNA-Seq results. Our results provide basic information about the genes involved in sex determination/differentiation and gametogenesis, and pave the way for further studies on reproduction and breeding in S. constricta and other marine bivalves.